2019
DOI: 10.24911/ijmdc.51-1568717752
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of the Saudi population about the role of the Emergency Rooms

Abstract: Background: The hospital emergency department (ED) is one of the most important components of the healthcare delivery system. This study aims to investigate the public awareness of the Emergency Rooms (ERs) in Saudi Arabia, what the public knows about the provided services, and if they know the difference between the outpatient clinics and the ERs. Methodology: It is a cross-sectional descriptive community-based study, carried out on 977 participants from all age groups, in different areas of Saudi Arabia, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…In addition, we found that the highest percentage of patients at the ED comprised the age groups of 15-29 and 30-44, respectively, at both crowding periods. This result is in agreement with the findings presented earlier [ 17 ], which showed that the largest percentage of patients visiting ED comprised middle-aged individuals. Furthermore, our study found that the percentage of Saudi patients present at the target government hospital was the highest in both crowding statuses.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, we found that the highest percentage of patients at the ED comprised the age groups of 15-29 and 30-44, respectively, at both crowding periods. This result is in agreement with the findings presented earlier [ 17 ], which showed that the largest percentage of patients visiting ED comprised middle-aged individuals. Furthermore, our study found that the percentage of Saudi patients present at the target government hospital was the highest in both crowding statuses.…”
Section: Discussionsupporting
confidence: 94%
“…These access blocks result in extended lengths of stay in inpatient departments and increased patient mortality [16]. In the Kingdom of Saudi Arabia, Alhussain et al [17] found that overcrowding was mainly caused by non-urgent visits to EDs due to insufficient community awareness of the ED's role and lack of access to primary healthcare services.…”
Section: Introductionmentioning
confidence: 99%
“…But there was no relationship with gender after adjustment to regression estimates. This is almost consistent with that of Alhussain et al, (2019).…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, our results showed that respondents aged 26-35 years showed lower satisfaction with the clarity of information (B = -3.62 and P < 0.05), relationship with staff (B = -1.84 and P < 0.1), and overall satisfaction (B = -2.54 and P < 0.05). Some previous studies showed that age is an essential determinant factor in determining satisfaction levels, where older participants had lower levels of satisfaction [10,11,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%